Kontestasi Konsepsi Religius dan Ritualitas Islam Pribumi Versus Islam Salafi di Sasak Lombok - Mohamad Iwan Fitriani (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2015)
This article focuses on the contestation of local Islam and Salafi at Narmada, West Lombok. This tension is an inevitable thing since they have a different way of understanding and realizing Islamic teaching. Local Islam wants the locality and universality co-present to actualize ideal Islamic teaching; on the contrary, Salafi wants to purify Islamic teaching from any kind of local traditions. Here, Local Islam of Sasak Narmada refers to Islam which has long interaction with several indigenous belief of Sasaknese manifested in Wetu Telu and Wetu Lima and Salafi refers to several (not all) Salafi’s followers who interact with local Muslims. This difference brings into contestation when Salafi popularises bid‘ah, syncretic or shirk for local Muslims adherent in one hand and local Muslims want to save Islamic teaching from Salafi. The contestation is classified into religious conceptions and ritual. Many Wetu Lime’s followers enjoy their religious conceptions and rituals without leaving several Wetu Telu traditions and without being afraid of falling into polytheism for a main reason that what they do is one means of manifesting universal Islamic values in local traditions and having no intention to be a polytheist. This study shows that looking for the meaning behind the conception or observed ritual is essential in diverse internal religious belief to spread peace in which theology needs to be accompanied by another perspective.